Child Development and Early Interaction: PERL Research Protocol, a Preventive Home Visiting Program, Randomized Controlled Trial in France - Buchheit, Sophie; Kabuth, Bernard; Colombo, Marie-Christine; Ligier, Fabienne (Frontiers in Psychiatry, 2021)
Background: Early childhood is a key period for reducing social inequalities in health. Parenting support and home visitation programs have proven their effectiveness. France's Protection Maternelle et Infantile (maternal and child welfare) services (PMIs) are at the heart of this primary prevention and may adapt their intervention to improve parenting support. We will describe the protocol of the PERL study. Method and design: PERL study is a single-center, randomized, controlled interventional trial. The aim is to assess the impact of a preventive home visiting program on the development of the young child and parent-baby interaction. These visits are made by PMI nurses to 64 families recruited randomly from the general population. All families who have a baby born after 35 weeks of pregnancy between September 2018 and December 2019 residing in the trial area were eligible. Participants were randomly allocated to the intervention group or the control group. The PMI nurses make 12 home visits in the first year, 6 the second year and 4 in the third and fourth years of the child's life. Primary and secondary outcomes are measured when the child is 4 and 24 months old. It includes (i) child's developmental milestones in particular language and socio emotional skills, (ii) early interaction, maternal sensitivity and attachment patterns, (iii) maternal psychopathology including depression. Discussion: This study aims to measure the impact of home visits by specifically-trained and supervised nurses on child’s development and parents-child interactions. Such interventions are complementary of other preventive programs addressing the impact of social inequalities on perinatal health. Placing nurses’ professional skills at the center of this project may prove effective and cost-saving intervention compared to existing programs. The challenge is to propose a prevention model that in keeping with the principle of reducing social inequalities in health by providing support from the earliest age through a public service. It is also to improve perinatal prevention public health politics. Trial registration: Current Clinical trial number is NCT03506971, registered the 24th April 2018 Keywords: Prevention, home visiting, early interaction, development of young child, randomized controlled trial